2004
DOI: 10.1111/j.0013-9580.2004.33103.x
|View full text |Cite
|
Sign up to set email alerts
|

The Pathology of Rasmussen Syndrome: Stages of Cortical Involvement and Neuropathological Studies in 45 Hemispherectomies

Abstract: Summary:Purpose: Rasmussen syndrome (RS) is a rare form of epilepsy characterized by progressive destruction of a single hemisphere. To characterize the profile of cortical involvement in RS, we studied the pathological changes in the cerebral cortex of 45 hemispherectomies performed at Johns Hopkins Hospital between 1985 and 2002.Methods: The patterns of pathologic changes and stages of cortical abnormalities were studied by histology and immunocy to chemistry methods. The burden of pathology (BP) was quantif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
174
0
10

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(197 citation statements)
references
References 26 publications
13
174
0
10
Order By: Relevance
“…The progression of the symptoms to significant neurological impairment usually occurs within months to few years. 17 Although RE causes are unkown, an autoimmune process has been suggested 2,9,12,16 and surgery is the treatment of choice to try to avoid mental retardation, dementia and death. 1 Electroencephalographic usually show a pattern of recurrent seizures, with activity over the central motor area.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The progression of the symptoms to significant neurological impairment usually occurs within months to few years. 17 Although RE causes are unkown, an autoimmune process has been suggested 2,9,12,16 and surgery is the treatment of choice to try to avoid mental retardation, dementia and death. 1 Electroencephalographic usually show a pattern of recurrent seizures, with activity over the central motor area.…”
Section: Introductionmentioning
confidence: 99%
“…7,17 In this study, we have reviewed the clinical, electrographic and post-operative evolution of patients with RE, considering long-term prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, consequences of perforin-and/or Fas-mediated killing are likely more relevant in advanced stages of inflammatory CNS disease. Neuronal loss is a dominant feature in chronic but not acute stages of RE (Bien et al, 2002;Pardo et al, 2004) and was observed only late after challenge (Fig. 1).…”
Section: Discussionmentioning
confidence: 93%
“…Pathologically, the salient features include chronic meningeal and parenchymal inflammation, consisting primarily of benign appearing T lymphocytes, both diffuse and nodular microglial cell proliferation, gliosis, and neuronal cell death. 36 The underlying pathogenesis of the disorder is still of some debate. Evidence supporting GluR3 autoantibody-induced injury is conflicting and there are cases in which such autoantibodies do not appear to exist; however, there is evidence to support a T-cell-mediated cytotoxicity targeting neurons in the disorder.…”
Section: Discussionmentioning
confidence: 99%